2001
DOI: 10.1021/jf010274l
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in Cooked Seafood Products:  Study on the Effect of Cooking on Total and Inorganic Arsenic Contents

Abstract: Total and inorganic arsenic contents were analyzed in cooked seafood products consumed in Spain during the period July 1997-June 1998: hake, meagrim, small hake, anchovy, Atlantic horse mackerel, sardine, bivalves, crustaceans, squid, and salted cod. Various cooking treatments were used (grilling, roasting, baking, stewing, boiling, steaming, and microwaving). The results obtained were compared statistically with those found previously in the same products raw, and they showed that after cooking there was a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 21 publications
6
40
1
3
Order By: Relevance
“…Questions about the usual consumption of foods high in inorganic arsenic including rice, Wsh, shellWsh, seaweed, and mushrooms were included. A review of the literature (Almela et al 2002;Dabeka et al 1993;Devesa et al 2001;MacIntosh et al 1997;Schoof et al 1999;Tao and Bolger 1999) suggests that the aforementioned foods are among the major sources of inorganic arsenic in the North American diet. As(III) and As(V) together constitute the inorganic species commonly ingested, and are believed to be the most toxic forms of arsenic found in the diet (Devesa et al 2001).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Questions about the usual consumption of foods high in inorganic arsenic including rice, Wsh, shellWsh, seaweed, and mushrooms were included. A review of the literature (Almela et al 2002;Dabeka et al 1993;Devesa et al 2001;MacIntosh et al 1997;Schoof et al 1999;Tao and Bolger 1999) suggests that the aforementioned foods are among the major sources of inorganic arsenic in the North American diet. As(III) and As(V) together constitute the inorganic species commonly ingested, and are believed to be the most toxic forms of arsenic found in the diet (Devesa et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…A review of the literature (Almela et al 2002;Dabeka et al 1993;Devesa et al 2001;MacIntosh et al 1997;Schoof et al 1999;Tao and Bolger 1999) suggests that the aforementioned foods are among the major sources of inorganic arsenic in the North American diet. As(III) and As(V) together constitute the inorganic species commonly ingested, and are believed to be the most toxic forms of arsenic found in the diet (Devesa et al 2001). There is some debate, however, about whether inorganic arsenic compounds, in contrast to organo-arsenic compounds, are found in seafood (Almela et al 2002;Schoof et al 1999).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, depending on the study, the effects of cooking on metal content in seafood are different and they may vary according to the element considered and its chemical speciation. Whereas Atta, El-Sebaie, Noaman, and Kassab (1997) demonstrated that the cooking process did not concentrate elements like Cd, Cu, Pb and Zn in the fish Tilapia nilotica, Devesa et al (2001) reported both reductions and increases in total arsenic contents after the cooking process in fish and bivalve, due either to solubilisation/volatilisation or concentration of the metalloid. The element concentrations in tissues after cooking appear also to depend on the type of cooking (Ersoy, Yanar, Kucukgulmez, & Celik, 2006;Perelló, Martí-Cid, Llobet, & Domingo, 2008) and the considered species, as, for example, 134 Cs is not concentrated in cooked mussel tissue (Metian et al, 2009) whereas it is in fish tissues (Burger et al, 2004).…”
Section: Raw Musselsmentioning
confidence: 96%
“…Table 3. Estimated daily intake of arsenic by the general population ( (Devesa et al 2001;Jelinek and Corneliussen 1977;Leblanc et al 2005;Mohri, Hisanaga, and Ishinishi 1990;Saipan and Ruangwises 2009;Sorvari et al, 2007;Watanabe et al 2004) The principal natural source is volcanic activity, with minor contribution by exudates from vegetation and wind-blow dust. Man-made emissions to air arise from the smelting of metals, the combustion of fuels, especially of low-grade brown coal, and the use of pesticides.…”
Section: Epidemiologymentioning
confidence: 99%